Perbandingan Aktivitas Antioksidan Infusa dan Dekokta Tanaman Galling (Cayratia trifolia (L.) Domin) - Angel Mangiwa; Mirna Maulidah; Tipalmaton R Patulen; Dhea K Kende; Ismail Ismail; Desy A Lestari; Maulita Indrisari; Lukman Muslimin (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
The number of patients with neurodegenerative disorders increased, especially in the productive age. The neurodegenerative disorder can be prevented by synthetic and natural antioxidants such as from plants. The herb of galling, Cayratia trifolia (L.) Domin), has long been traditionally used to prevent degenerative diseases by drinking decoction. The current study aimed to compare the antioxidant capability between infusion and decoction of galling against DPPH. The herbs were extracted with two methods, namely infusion, and decoction. This study used 7 different serial concentrations ranging 7.81 till 500 µg/mL, while the optical density was recorded at 515 nm using a spectrophotometer. The results demostrated that both infusion and decoction have antioxidant activity against DPPH with IC50 values of 87.55±1.01 (strong category) and 65.38±2.26 µg/mL (strong category), respectively. There was a statistically significant (p<0.05) between the IC50 values of infusion and decoction. In conclusion, galling is efficacious as an antioxidant source for preventing and treating degenerative diseases.